Kebun gizi sebagai upaya pemenuhan gizi berbasis masyarakat - Dwi Endah Kurniasih; Joko Adianto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Food garden as a community-based strategy to meet consumption needsPurposeThis study aims to assess the Kebun Gizi program which has been running for two years.MethodsThis descriptive study involved 80 heads of family. Sampling method was simple random sampling. This study was conducted in December 2014 in Kebun Gizi, Jebres Surakarta. Instruments used were in the form of questionnaire. The data were analysed using descriptive method to find out the benefit of Kebun Gizi felt by the community, especially which was related to the eating behaviour of vegetables/fruits, planting behaviour and motivation and cost saving aspect.ResultsThe results showed all respondents were participants of Kebun Gizi. Among the respondents, 96% had willingness to invite others. Another impact was that it could be a joint movement to plant vegetables in the yard, as was mentioned by 88% of the respondents. There were 68% of respondents argued that Kebun Gizi could be one form of food security and 67.5% already felt that following the program could save the cost of household expenses. The average saving of household expenses on 67 families was Rp. 3.350.000,- per month and Rp. 40.200.000,- per year.ConclusionKebun Gizi has a positive impact, especially which is related to the participation in nutrition fulfillment efforts in the community.